The Achaemenid Persian empire in the west and Persian-period Yehud - Ristau, Kenneth A. (My University, 2018)
The disruption and caesura caused by the destruction of Jerusalem in 587 BCE are not easily overstated. In addition to precipitating severe ideological tremors that undermined the traditional political and religious claims of Jerusalem's inviolability and Yahweh's perpetual support for the house of David, the architectonic and demographic evisceration of the city and its environs as well as the concomitant collapse of the kingdom of Judah were undeniably dramatic. In the wake of destruction and collapse, Judean society splintered. On the one hand, the Babylonian campaigns in 597 and 587 produced exiles and refugees, which created or added to Diaspora communities throughout the greater Near East that had been growing and developing since the Neo-Assyrian period (ca. 732-604 BCE). On the other hand, the remnants left in the land coalesced into two distinct enclaves: one in Benjamin, centered on Mizpah, and a second in the highlands south of Jerusalem. These enclaves consisted of a few landholding families, an impoverished populace, and disenfranchised refugees with tribal sheikhs, clan chiefs, and family heads as the local leadership.
Keywords: Bible; Middle East history